2020
DOI: 10.1177/0015732520970441
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Export Diversification, Economic Complexity and Economic Growth Cycles: Global Evidence

Abstract: This article investigates the dynamics of export diversification, economic complexity and economic growth cycles. By applying several econometric techniques for estimating a panel data set of 70 economies over the period from 1996 to 2014, the results have been threefold. First, there is Granger bi-directional causality between economic complexity and export diversification, while unidirectional Granger causality exists from economic complexity to economic growth cycles. Second, the result attained from the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…We complement the previous analysis by investigating in this section whether the effect of economic complexity on poverty can translate through the economic growth volatility channel. This is because on the one hand, a recent literature has shown that economic complexity is associated with lower aggregate output volatility (e.g., Güneri and Yalta, 2020;Miranda-Pinto, 2021), lower firms' output volatility (e.g., Maggioni et al, 2016), and dampens economic growth cycles (e.g., Canh and Thanh, 2020). On the other hand, a large body of the literature has now well established that greater macroeconomic volatility (e.g., output volatility) due, inter alia, to external shocks (e.g., financial crises and economic crises such as severe commodity prices shocks) adversely affects poor people, and raises poverty in developing countries 6 .…”
Section: Further Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We complement the previous analysis by investigating in this section whether the effect of economic complexity on poverty can translate through the economic growth volatility channel. This is because on the one hand, a recent literature has shown that economic complexity is associated with lower aggregate output volatility (e.g., Güneri and Yalta, 2020;Miranda-Pinto, 2021), lower firms' output volatility (e.g., Maggioni et al, 2016), and dampens economic growth cycles (e.g., Canh and Thanh, 2020). On the other hand, a large body of the literature has now well established that greater macroeconomic volatility (e.g., output volatility) due, inter alia, to external shocks (e.g., financial crises and economic crises such as severe commodity prices shocks) adversely affects poor people, and raises poverty in developing countries 6 .…”
Section: Further Analysismentioning
confidence: 99%
“…human development (e.g., Le Caous and Huarng, 2020), reduce economic growth volatility (e.g., Güneri and Yalta, 2020;Maggioni et al, 2016;Miranda-Pinto, 2021), dampen economic growth cycles (e.g., Canh and Thanh, 2020) and increase labor share notably in the context of (e.g., Arif, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…More generally, complex goods, i.e., sophisticated goods are those that have a high knowledge content, i.e., those with a high human capital intensity, (e.g., Bustos et al, 2012;Hausmann and Hidalgo, 2009;Hausmann and Hidalgo, 2011;Hidalgo, 2009). Additionally, some studies (e.g., Güneri and Yalta, 2020;Maggioni et al, 2016;Miranda-Pinto, 2021) have obtained empirically that complex economies 12 experience lower economic growth fluctuations, or lower economic growth cycles (e.g., Canh and Thanh, 2020).…”
Section: Effect Of Human Capital On Economic Growth Volatilitymentioning
confidence: 99%
“…In turn, greater export diversification can lead to lower output volatility and hence increase countries' capacity to withstand external shocks (e.g., Balavac et al, 2016;Haddad et al, 2013). Similarly, greater economic complexity is associated with lower economic growth volatility (e.g., Güneri and Yalta, 2020;Maggioni et al, 2016;Miranda-Pinto, 2021) as well as lower economic growth cycles (e.g., Canh and Thanh, 2020). Given that export resilience could be greater in the context of lower output volatility, we infer that trade policy liberalization would ultimately be associated with greater export resilience through its positive effect on innovation, export product diversification (or economic complexity).…”
Section: Model Specificationmentioning
confidence: 99%